Uncovering Intention to Adopt Self-Checkout Through Technology Readiness: Empirical Study of Retail Customers - Ibrahim, Muhammad Hanif; Amelia, Widya Ayu; Syahafin, Ansari A. (Universitas Airlangga, 2025)
Objective: The objective of this study is to examine the factors that influence the intention to adopt self-checkout in a retail context. Design/Methods/Approach: This study employs the PLS-SEM method, with a total of 356 respondents selected using purposive sampling. Findings: The dimensions of technology readiness have been shown to have a significant effect on expected ease of use and expected usefulness, except discomfort, which did not affect expected usefulness. In addition, autonomous motivation is proven to have a significant positive effect on expected ease of use and expected usefulness, despite controlled motivation having no impact on either expected ease of use and expected usefulness. Consequently, expected ease of use and expected usefulness significantly improve attitudes toward self-checkout system. Originality/Value: This research integrates three theories, technology readiness, technology acceptance model, and self-determination theory in predicting self-checkout Practical/Policy implication: For retailers looking to implement a self-checkout system, our research provides insights into the importance of adequate resources and support to facilitate user adoption. Retailers can leverage these findings to develop effective communication strategies highlighting the benefits of self-checkout through in-store and online advertising, resource updates, and employee training.